Comparison of the efficacy of two human fibrinogen concentrates to treat dilutional coagulopathy in vitro. (3rd April 2018) - Haas, Thorsten; Cushing, Melissa M.; Asmis, Lars M.
Abstract: Both congenital and acquired fibrinogen deficiency can be safely treated with administration of fibrinogen concentrate. The aim of this study was to test the efficacy of a new fibrinogen product (Fibryga) compared to a licensed product (Haemocomplettan) in an in vitro model of dilutional coagulopathy. Ten blood specimens from healthy volunteers were diluted 1:1 with balanced crystalloid solution and subsequently supplemented with each fibrinogen concentrate at a dose replicating in vivo supplementation (50 mg kg −1 ). Changes in clot firmness (FIBTEM and EXTEM assay), as well as changes in the fibrinogen antigen level, fibrinogen activity, factor XIII level and fibronectin levels were assessed at baseline, after dilution and after adding fibrinogen concentrate. There was no significant difference between the drugs in their in vitro ability to improve clot firmness in the FIBTEM assay (Fibryga: mean MCF 14.4 mm (SD 3.4 mm) vs. Haemocomplettan: MCF 14.1 mm (2.4); p  = .584). Fibryga led to significantly higher clot firmness in EXTEM MCF: 56.7 mm (3.8) vs. 53.7 mm (3.7); p  < .001). Distinct differences between FXIII levels (significantly higher in Fibryga; mean 40.9% (6.2%) vs. 31.0% (6.2%); p  < .001) and fibronectin levels (significantly higher in Haemocomplettan; mean 0.008 g L −1 (SD 0.002 g L −1 ) vs. 0.002 g L −1 (SD 0.002 g L −1 ; p  < .001) were observed between products. This is the first study to demonstrate that Fibryga and Haemocomplettan have similar efficacy in improving clot firmness in a dilutional hypofibrinogenemia model in vitro .